P18 Scaling up hepatitis C community-based treatment services to address healthcare inequalities in Sussex. (28th September 2020) - Crofton-Biwer, J; Readhead, S; Cresswell, D
Abstract : Introduction: Patient engagement with testing and treatment is a barrier to eliminating Hepatitis C Virus (HCV). Due to healthcare inequalities patients with HCV often struggle to engage with traditional acute specialist services, and are undiagnosed and untreated as a result. Informed by the success and learning of the ITTREAT project (O'Sullivan et al, 2020), the challenge was to scale up community nurse-led services. This would also increase the range of staff engaging those at risk of HCV providing new opportunities for access. In 2017-2018 HCV treatment was only available in six community locations across Sussex resulting in 12% of patients starting treatment in the community. We planned to collaborate with a range of new community partner providers external to the NHS, to provide education and a one-stop test and treat service. Aims: Address patient healthcare inequalities by scaling up community nurse-led services to increase access to HCV treatment in Sussex. Methods: Our approach was to scale up services, through systems leadership in a collaborative network model. Drug and alcohol services and homeless hostels were targeted due to their strong existing relationships with people who inject drugs, a group identified as most at risk for HCV transmission in our region. Key to implementation was regular reiteration, evaluation and feedback across the network, utilising 'Plan, Do, Study, Act (PDSA) cycles to evolve solutions to the needs of each provider and their clients. We forged a common purpose, combined with a supportive culture to overcome challenges as they emerged. We focused on the positive impacts of our work and the values the nursing team have established to connect and build strong relationships with the staff of our partner organisations. We focused on a number of areas including training, development, patient and staff needs; working collaboratively to find solutions and establishing working groups where needed. A data dashboard, 'one version of the truth, ' was shared across all organisations, to inspire discussion about further improvements. Results: Community locations increased from six in 2017–2018 to 17 in 2019–2020 resulting in a five fold increase in the number of patients treated in the community (n=34 vs. n=154) (figure 1 ). Currently 50% of our HCV treatment is community-based compared to 12% prior to our initiative. Conclusion: Working collaboratively with stakeholders can substantially scale up community-based HCV treatment by delivering an integrated and personalised service. Wider adoption of such models through a collaborative and reiterative approach could help achieve HCV elimination.